First, let's simplify the expression step by step using the rules for multiplying and dividing.
Step 1: Multiply -2 and 1/5:
(-2) × (1/5) = -2/5
Step 2: Divide -2/5 by 2/3:
(-2/5) ÷ (2/3) = (-2/5) × (3/2) = -6/10 = -3/5
Step 3: Multiply -3/5 by -5/6:
(-3/5) × (-5/6) = (3/5) × (5/6) = 15/30 = 1/2
Step 4: Divide 1/2 by 3/4:
(1/2) ÷ (3/4) = (1/2) × (4/3) = 4/6 = 2/3
Therefore, the value of the expression (-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4) is 2/3.
Use the properties of operations and rules for multiplying and dividing to solve: (−2)×(1/5)÷(2/3)×(−5/6)÷(3/4) (1 point)
1 answer